Recovery of low volumes of wear debris from rat stifle joint tissues using a novel particle isolation method. (15th April 2018) - Patel, J.; Lal, S.; Nuss, K.; Wilshaw, S.P.; von Rechenberg, B.; Hall, R.M.; Tipper, J.L.
Graphical abstract: Abstract: Less than optimal particle isolation techniques have impeded analysis of orthopaedic wear debris in vivo . The purpose of this research was to develop and test an improved method for particle isolation from tissue. A volume of 0.018 mm 3 of clinically relevant CoCrMo, Ti-6Al-4V or Si3 N4 particles was injected into rat stifle joints for seven days of in vivo exposure. Following sacrifice, particles were located within tissues using histology. The particles were recovered by enzymatic digestion of periarticular tissue with papain and proteinase K, followed by ultracentrifugation using a sodium polytungstate density gradient. Particles were recovered from all samples, observed using SEM and the particle composition was verified using EDX, which demonstrated that all isolated particles were free from contamination. Particle size, aspect ratio and circularity were measured using image analysis software. There were no significant changes to the measured parameters of CoCrMo or Si3 N4 particles before and after the recovery process (KS tests, p > 0.05). Titanium particles were too few before and after isolation to analyse statistically, though size and morphologies were similar. Overall the method demonstrated a significant improvement to current particle isolation methods from tissue in terms of sensitivity and efficacy at removal of protein, and has the potential to be used for the isolation of ultra-low wearing total joint replacement materials from periprosthetic tissues. Statement of Significance: This research presents a novel method for the isolation of wear particles from tissue. Methodology outlined in this work would be a valuable resource for future researchers wishing to isolate particles from tissues, either as part of preclinical testing, or from explants from patients for diagnostic purposes. It is increasingly recognised that analysis of wear particles is critical to evaluating the safety of an orthopaedic device.